Pembayaran Qris Dan Pemasaran Media Sosial Untuk Keunggulan Kompetitif Rm Bu Entoy - Greisa Chairunnisa; Rudi Samuel Parlindungan; Santi Rimadias (CV. ITTC INDONESIA, 2024)
This community service activity focuses on increasing the competitiveness of RM Bu Entoy, a business that lacks cashless payment options and an effective social media marketing strategy. Offering cashless payments is a modern, customer-centric approach that sets businesses apart in competitive markets. Unfortunately, RM Bu Entoy does not currently have such an option, thus providing opportunities for improvement. This service activity aims to assist RM Bu Entoy in adopting cashless payment methods and the importance of effective social media marketing for MSMEs. Social media serves as a direct channel for interaction, relationship building, and market expansion. The methods used are observation, interviews, surveys, and assistance in this community service activity. The results achieved are in line with the project objectives, as RM Bu Entoy successfully integrated QRIS for cashless payments and utilized social media effectively for marketing, thus contributing to its overall competitiveness and market reach.